A1.7 Serum cytokine changes in rituximab-treated rheumatoid arthritis patients. (31st January 2014) - de Jong, T D; Vosslamber, S; de Jager, W; Raterman, H; Voskuyl, A E; Gelderman, K A; Verweij, C L
Abstract : Background: Although B cell depletion therapy with rituximab is successful in the majority of rheumatoid arthritis (RA) patients, 30–40% of patients do not respond. The mechanism behind this is yet unknown, as B cell depletion generally takes place in all patients. This study aims to explore changes in serum cytokines during rituximab therapy in established RA patients. Methods: Serum was collected from 18 established RA patients before and after 1, 3, 6, 9 and 12 months of rituximab therapy. A panel of thirty-four cytokines was measured in a multiplex immunoassay. Patients with a change in disease activity score (∆DAS28) >1.2 after 6 months were considered responders. Results: During rituximab therapy, CXCL13 significantly decreased in all patients (median 1.9-fold decrease (IQR 1.4-3.3)), irrespective of responder status. This coincided with B cell depletion, suggesting that CXCL13 reflects B cell levels in the circulation. No differences were observed between responders and non-responders after 1 and 3 months of therapy. However, at 6, 9 and 12 months, CXCL10 dynamics differed significantly between responders and non-responders (R vs. NR, T6/T0 p = 0.004, T9/T0 p = 0.003, T12/T0 p = 0.001). Non-responders showed an increase compared to baseline, whereas responders did not. The change in CXCL10 correlated to the ∆DAS28 at 6 months, indicating that this reflects disease activity rather than a mechanistic effect of rituximab. Most strikingly, IL-12 was undetectable in most non-responders until 6 months, but showed a substantial increase after 9 months of therapy, which did not occur in the responders (R vs. NR T9/T6 p = 0.030, Fisher's exact p = 0.049). The change in IL-12 did not correlate to ∆DAS28. Conclusions: This study shows that during rituximab therapy, cytokine changes occur in the patient serum, both related and unrelated to the clinical response. CXCL13 seems to reflect B cells levels in the circulation, whereas the dynamics of CXCL10 and IL-12 during therapy are regulated differently between responders and non-responders during rituximab treatment. These findings indicate different pharmacological effects of rituximab between responders and non-responders. This research was supported by the Center for Translational Molecular Medicine (CTMM) and the Dutch Arthritis Foundation (TRACER).